Application of ultrasonic pretreatment for coking coal flotation and its mechanism. Issue 3 (4th March 2022) - Chen, Songjiang; Tao, Xiuxiang; Tang, Longfei; Dong, Fang; Gui, Dongjiao
ABSTRACT: This paper focuses on enhancing the flotation of coking coal with ultrasonic pretreatment and the corresponding improving mechanism. The effects of ultrasound on the coal surface properties and the dispersion of oil collector in flotation slurry were fully studied. The SEM, FTIR and XRF analyses indicated that, after the ultrasonic pretreatment, the fine particles covered on coarse coal particles were removed and the elements forming gangue minerals were decreased, which improved the surface hydrophobicity of the coal sample. What's more, the optical microscope measurements for collector dispersion showed that the size of diesel oil droplets was greatly reduced after the ultrasonic treatment, suggesting the enhanced dispersion of collector in flotation pulp. As a result of synergistic effects of ultrasonic treatment on the coal surface cleaning and promotion of collector dispersion in pulp, a maximum combustible matter recovery of 79.79% was attained with the flotation process 2 (i.e., the ultrasonic treatment was performed after the addition of collector to the pulp). Furthermore, the enhanced collector dispersion in pulp caused by the ultrasonic treatment may be conducive to reduce the collector consumption in actual flotation practice.